Retrospective study of maternal and fetal neonatal outcome of dengue virus infection during pregnancy at a tertiary care hospital - Samyukthanjali, Mulakala; M., Munikrishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Dengue fever, a viral infection prevalent in tropical and subtropical areas, exhibits a varied clinical course. While a significant portion of infected individuals remain asymptomatic, the illness can range from a minimal febrile illness to life-threatening dengue shock syndrome. The most common presentation is a self-resolving febrile episode lasting 2-7 days, accompanied by severe headaches, myalgia, arthralgia, nausea, vomiting, and fatigue. However, a critical phase can follow the initial defervescence, characterized by severe abdominal pain, persistent vomiting, and hemorrhagic manifestations. Early recognition and management of severe dengue are essential for optimal outcomes. Females within their reproductive window residing in endemic regions of dengue are susceptible to infection. This study seeks to elucidate the association between dengue virus infection with pregnancy followed with subsequent neonatal outcome, maternal complications. Methods: A retrospective observational study at was conducted at R. L. Jalappa Hospital and Research Centre, Kolar, India. The study examined the medical records of 28 pregnant women diagnosed with Dengue fever between January 2022 and January 2024. Results: The study participants mean age was 25.6±5.2 years. Out of total, 50% cases were primi gravida and remaining 50% cases were multi gravida. Of total, 39% cases were required platelet transfusion. Among the study participants, total 11 (39.3%) cases ad presence of PPH, 10 (35.7%) cases delivered preterm babies and 1 maternal death was noted due to dengue fever. Of total, 17.9% fetal distress occurred, 42.9% baby required NICU admission after birth and 28.8% IUD were noted. Conclusions: Severe dengue during pregnancy may raise the risk of obstetric haemorrhage, preeclampsia, and eclampsia, as well as increasing the chance of foetal distress, caesarean delivery, and mother death.